PRELIMINARY STUDY: THE INFLUENCE OF MICRO CLIMATE ASPECTS TO MINIMALIST LANDED HOUSES AND A VERNACULAR STILT HOUSE (CASE STUDY: HARMONIA AND BELLAROSA CLUSTERS, KAMPUNG NAGA HOUSE, INDONESIA) - Handajani Asriningpuri; Fajar Kurniawati; Aliviana Demami (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2017)
Today, minimalist building style is considered appropriate to the reasons of: the high price of land and materials. Moreover, vernacular style inspires designers to categorisize it as a simple architectural type that is responsive to the context of micro climate. Both are modest style as undecorated building. This study aimed to communicate research result on the influence of micro climate aspects to both mentioned architectural types. Descriptive-analitic approach applied in this article is to identify the differencies between the features of minimalist landed houses (Harmonia and Bellarosa Clusters) and vernacular stilt house (Kampung Naga) components which are influenced by micro climate aspects. The result of study is that the decreasing and increasing of indoor temperature are determined by wall type and material; ventilation system; roof, eave and bottom structure types; geographical position; openings dimension.Keywords: micro climate, minimalist, vernacular architecture.